Percentage (%) of maximum prey size (mm) of eight prey groups in the gizzard of eiders during winter in Danish waters. - Karsten Laursen (556576); Anders Pape Møller (7913618) (2021)
Percentage (%) of maximum prey size (mm) of eight prey groups in the gizzard of eiders during winter in Danish waters.